Pengaruh Konsentrasi dan Kecepatan Pengaduk Pada Proses Desalinasi Air Payau Menggunakan Kitosan Kulit Udang Vaname - Kasmudin, Karim; Fitria, Fitria; Mahyudin, Faizal; Pascal, Aditya (Journal of Science and Education Research, 2023)
Desalination (removal of salt content) of salt or brackish water into fresh water is another way to obtain fresh water. The two most widely practiced methods are distillation (distillation), heating seawater until it evaporates and then condensing to get fresh water and reverse osmosis, seawater at high pressure through a thin membrane to pass water molecules. Another method that can be used in the desalination process is the adsrobtion process. One of the media that can be used in the adsrobtion process is chitosan. This research is carried out by the bacth method with two variables, the first variable concentration, namely 800, 1600, 2400, 3200 and 4000 ppm. The second variable is the stirring time with variations, namely 100, 200, 300, 400 and 500 rpm. Based on the results of studies that have been carried out, the best concentration of shrimp skin chitosan is at a concentration of 4000 mg / L or the addition of 200 mg of chitosan in 0.25 L of brackish water. At this concentration, the absorbent can reduce the salinity of brackish water by 86.6694% and for the best stirring speed the shrimp shell chitosan is at a speed of 300 rpm with the addition of 1000 mg of chitosan in 0.25 L of brackish water. At this stirring speed, the adsorbent can reduce the salinity of brackish water by 82.6335%.